Reflection of Afghan Ethnic Identity in A Thousand Splendid Suns by Khaled Hosseini - Pondelíková, Ivana; Pecníková, Jana (Acta humanitarica academiae Saulensis, 2025)
The article deals with a modern phenomenon, which is identity and its kinds. The presented research is set in Afghanistan and is based on an analysis of the novel A Thousand Splendid Suns by the Afghan-American physician Khaled Hosseini, who is currently the most famous and popular author writing about Afghanistan. A Thousand Splendid Suns is Hosseini’s second novel, which tells the story of two women, Mariam and Laila, from different generations and social classes, whose lives are united by marriage to one man and the war that forced millions to flee abroad. Violence, fear, the injustice treatment of women, and identity issues, as well as faith, hope, the protection of the family and lasting values, are concretized in the struggle for survival. In the presented research, we examined two kinds of identity, particularly ethnic and religious ones as they are essential for forming an Afghan identity. We concentrated on the formation of Afghan identity in the historical context, because the history of Afghanistan has greatly influenced its development. Several nations have tried to conquer this country and its people, but without any success. Afghanistan is considered a cemetery of great empires. Moreover, geographically, it is a mountainous country with a harsh climate, in which it can be difficult for foreigners to live or survive. Even Alexander the Great, the Mongols, the British, the Soviets, or NATO forces did not have it easy in Afghanistan. In the research, we focused on two significant historical events that strongly influenced the formation of Afghan identity, especially in the era from the Soviet invasion to the Taliban up to the present days. For Slovak readers, due to a similar experience with the Soviet invasion (1968–1989), the topics of unfreedom, hiding personal identity, persecution, adapting and accepting a regime and living under the domination of another nation are well-known. It necessary to acquaint readers with the recent history of Afghanistan so that they could identify with the fates of the main characters who lived in an unstable, ever-changing, and multi-ethnic society, where the government regime, name and symbols are constantly changing, thus, making it difficult to create a unified national identity. Afghanistan is a “troubled country” that gives the impression of enduring constant chaos, freedom, conflicts and war. At the same time, it is an exotic and oriental country that is still unknown for Westerners. Hosseini’s role is not to question the Western view of Afghanistan, but rather to enrich it. The writer brings new knowledge to readers and turns ordinary Afghans into loving people who long for a dignified life.
Keywords: identity; national identity; transnational identity; ethnic identity; religious identity; Afghan identity; A Thousand Splendid Suns; Khaled Hosseini